Enhanced production of IL-17A in patients with severe asthma is inhibited by 1α,25-dihydroxyvitamin D3 in a glucocorticoid-independent fashion - Nanzer, Alexandra M.; Chambers, Emma S.; Ryanna, Kimuli; Richards, David F.; Black, Cheryl; Timms, Peter M.; Martineau, Adrian R.; Griffiths, Christopher J.; Corrigan, Christopher J.; Hawrylowicz, Catherine M. (Journal of allergy and clinical immunology, 2013)
TH17 cells are proposed to play a role in the pathology of asthma, including steroid-resistant (SR) disease. We previously identified a steroid-enhancing function of vitamin D in patients with SR asthma in restoring the impaired response to steroids for production of the anti-inflammatory cytokine IL-10. We sought to investigate the production of the TH17-associated cytokines IL-17A and IL-22 in culture in patients with moderate-to-severe asthma defined on the basis of their clinical response to steroids and the susceptibility of this response to inhibition by steroids and the active form of vitamin D, 1α,25-dihydroxyvitamin D3 (1,25[OH]2D3). PBMCs were stimulated in culture with or without dexamethasone and 1,25(OH)2D3. A cytometric bead array, ELISA, and intracellular cytokine staining were used to assess cytokine production. The role of CD39 in inhibition of the TH17 response was studied by using quantitative real-time PCR, flow cytometry, and addition of the antagonist POM-1 to culture. Asthmatic patients synthesized much higher levels of IL-17A and IL-22 than nonasthmatic control subjects, with patients with SR asthma expressing the highest levels of IL-17A. Glucocorticoids did not inhibit IL-17A cytokine expression in patients and enhanced production in cultures from control subjects. Treatment with 1,25(OH)2D3 with or without dexamethasone significantly reduced both IL-17A and IL-22 levels. An antagonist of the ectonucleotidase CD39 reversed 1,25(OH)2D3-mediated inhibition of the IL-17A response. Patients with severe asthma exhibit increased levels of TH17 cytokines, which are not inhibited by steroids. 1,25(OH)2D3 inhibits TH17 cytokine production in all patients studied, irrespective of their clinical responsiveness to steroids, identifying novel steroid-enhancing properties of vitamin D in asthmatic patients.